PENGARUH TIPOLOGI STRATEGI KOMPETITIF, KEMATANGAN TEKNOLOGI SISTEM INFORMASI DAN UKURAN PERUSAHAAN TERHADAP RESPON STRATEGIK DALAM MENGHADAPI GLOBALISASI - ROSINTAN SIPAYUNG (JURNAL ILMIAH KOHESI, 2018)
This research is about Maturity Effect of Information Technology and Strategic Response Against Company Size Facing Globalization. There are four variables in this research that includes independent variables and the dependent variable. Maturity and Size Information Technology Company is the independent variable, while the Strategic Response Facing Globalization is the dependent variable. Data studied were the primary data from research kuisiner. Data were analyzed by multiple regression analysis using SPSS. As a result, research shows that all independent variables, jointly significant effect on variable Y. simultaneous test results indicate that the column sig.0.000 of <0.05 level of significant (a). Partial assay results indicate that the Information Technology Maturity significant effect on Strategic Response Facing Globalization. Adjusted R Square obtained in this study was 0.49.